2008
DOI: 10.1090/s0002-9947-08-04466-8
|View full text |Cite
|
Sign up to set email alerts
|

On closed sets with convex projections under narrow sets of directions

Abstract: Abstract. Dijkstra, Goodsell, and Wright have shown that if a nonconvex compactum in R n has the property that its projection onto all k-dimensional planes is convex, then the compactum contains a topological copy of the (k − 1)-sphere. This theorem was extended over the class of unbounded closed sets by Barov, Cobb, and Dijkstra. We show that the results in these two papers remain valid under the much weaker assumption that the collection of projection directions has a nonempty interior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Barov, Cobb, and Dijkstra [1] were subsequently able to construct an extension of that result over the class of unbounded closed sets and [2] concerns the Hilbert space variant of the problem. In [3] we showed that the results in [8] and [1] remain valid if we make the much weaker assumption that the collection of projection directions that produce convex shadows has a nonempty interior.…”
Section: If C Is a Closed Weak P-imitation Of B With C = B Then C ∩ mentioning
confidence: 93%
See 4 more Smart Citations
“…Barov, Cobb, and Dijkstra [1] were subsequently able to construct an extension of that result over the class of unbounded closed sets and [2] concerns the Hilbert space variant of the problem. In [3] we showed that the results in [8] and [1] remain valid if we make the much weaker assumption that the collection of projection directions that produce convex shadows has a nonempty interior.…”
Section: If C Is a Closed Weak P-imitation Of B With C = B Then C ∩ mentioning
confidence: 93%
“…Observe that [3,Theorem 18] corresponds to Theorem 1 with the additional assumption that P is open in G n−k (R n ). The method we use is to show that if P satisfies the premises of Theorem 1, then int P contains a nonempty open subset that satisfies the premises of [3,Theorem 18]; see Theorem 13.…”
Section: If C Is a Closed Weak P-imitation Of B With C = B Then C ∩ mentioning
confidence: 99%
See 3 more Smart Citations